(untitled) (Medical Forum Monthly, 2021)
Objective: To compare the fetal outcome in patients taking metformin and insulin for control of gestational diabetes mellitus. Study Design: Randomized Controlled trial study. Place and Duration of Study: This study was conducted at the Department of Obstetrics & Gynaecology, Shahida Islam Teaching Hospital, Lodhran from 1st January 2020 to 31st December 2020. Materials and Methods: Total 134 pregnant women with gestational diabetes mellitus of gestational age >20 weeks of age 18-40 years were selected. Patients with multiple pregnancies, hypersensitivity to metformin or insulin, IUGR, known diabetics and CRF were excluded. Patients in the group A were given tablet metformin 500mg orally and group B were given insulin by subcutaneous route. Serum sugar levels were done regularly for glycemic control and dose adjustment. Patients were followed regularly by the researcher herself till delivery at which fetal outcome (preterm birth, NICU admission and neonatal hypoglycemia) was noted. Results: The mean age of women in group A was 27.52 ± 6.02 years and in group B was 26.70 ± 6.56 years. Majority of the patients 95 (70.90%) were between 18 to 30 years of age. The mean gestational age of women in group A was 28.02 ± 3.45 weeks and in group B was 28.43 ± 3.52 weeks. In this study, there were 05 (7.46%) had preterm birth with metformin while 15 (22.39%) had preterm birth with insulin (p-value = 0.015). There were NICU admission in 12 (17.91%) neonates with metformin and 20 (29.85%) neonates with insulin. Neonatal hypoglycemia was seen in 08 (11.94%) neonates with metformin and 20 (29.85%) neonates with insulin. Conclusion: This study concluded that fetal outcome is better with metformin use in gestational diabetes mellitus as compared to insulin use.